2012
DOI: 10.1051/0004-6361/201118339
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic diffusion of the Vesta family induced by close encounters with massive asteroids

Abstract: We numerically estimate the semi-major axis chaotic diffusion of the Vesta family asteroids induced by close encounters with 11 massive main-belt asteroids: (1) Ceres, (2) Pallas, (3) Juno, (4) Vesta, (7) Iris, (10) Hygiea, (15) Eunomia, (19) Fortuna, (324) Bamberga, (532) Herculina, (704) Interamnia. We find that most of the diffusion is caused by Ceres and Vesta. By extrapolating our results, we are able to constrain the global effect of close encounters with all main-belt asteroids. A comparison of this dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 22 publications
4
35
0
Order By: Relevance
“…Orbital diffusion caused by close encounters between small asteroids and one of the major bodies in the main belt, (1) Ceres 1 , (2) Pallas, (4) Vesta, and (10) Hygiea was already shown to be a mechanism able to produce long-term change in the proper elements of asteroids in the proximity of the orbits of (1) Ceres and (4) Vesta (Carruba et al 2003(Carruba et al , 2007Delisle & Laskar 2012). The change in semi-major axis, eccentricity, and inclination caused by the long-term effect of close encounters with (4) Vesta may have contributed to the diffusion of some of the V-type asteroids currently outside the Vesta family whose orbits could not be easily explained in terms of migration from the Vesta family caused by other mechanisms, such as diffusion by the Yarkovsky and YORP effects, interaction with mean-motion and secular resonances, or both.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Orbital diffusion caused by close encounters between small asteroids and one of the major bodies in the main belt, (1) Ceres 1 , (2) Pallas, (4) Vesta, and (10) Hygiea was already shown to be a mechanism able to produce long-term change in the proper elements of asteroids in the proximity of the orbits of (1) Ceres and (4) Vesta (Carruba et al 2003(Carruba et al , 2007Delisle & Laskar 2012). The change in semi-major axis, eccentricity, and inclination caused by the long-term effect of close encounters with (4) Vesta may have contributed to the diffusion of some of the V-type asteroids currently outside the Vesta family whose orbits could not be easily explained in terms of migration from the Vesta family caused by other mechanisms, such as diffusion by the Yarkovsky and YORP effects, interaction with mean-motion and secular resonances, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Laskar et al (2011) showed that when the five major bodies were included in simulations with all the planets, surprisingly, not only the orbits of the major asteroids were more chaotic, but even the precision with which the orbital elements of the Earth are known was limited to 50 Myr. Delisle & Laskar (2012) investigated the orbital mobility in the Vesta family region caused by close encounters with eleven major asteroids, and found that most of the mobility is caused by encounters with (4) Vesta and (1) Ceres, and is on the order of magnitude of what is found in previous works (Carruba et al 2003(Carruba et al , 2007. Delisle & Laskar (2012) estimated that close encounters dominated the orbital mobility of minor bodies with respect to the Yarkovsky and YORP effects only for large objects, with increasingly limited diameters when longer timescales were considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…timescales of 250 Myr, according to Delisle & Laskar (2011; see also a discussion in Carruba et al 2003). Using the relationship…”
Section: Dynamical Mapsmentioning
confidence: 99%